2013
DOI: 10.1007/s00520-013-1756-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pain education in cancer patients

Abstract: Further large, high-quality RCTs using a placebo control such as attention control are required to investigate whether pain education has a true efficacy on pain control or is a placebo effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…On the other hand, a lot of effort has been made to educate the patients preoperatively about the operation and the associated sequellae in order to effectively control the pain. Even in cancer patients, this approach seems to be effective as this was shown in a recent meta-analysis of randomized controlled trials (RCT) [ 10 ]. Similar results were presented previously by others [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a lot of effort has been made to educate the patients preoperatively about the operation and the associated sequellae in order to effectively control the pain. Even in cancer patients, this approach seems to be effective as this was shown in a recent meta-analysis of randomized controlled trials (RCT) [ 10 ]. Similar results were presented previously by others [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further research is warranted to better evaluate PEP effectiveness, this could be done by optimizing appropriate intervention content and by selecting relevant and realistic assessment tools. If pain intensity still remains an inescapable tool to evaluate education program effectiveness, 69,70 recent studies advance support for the importance of assessing newly developed outcome criteria, such as participation in pain management. By forming effective partnerships with clinicians, patients learn advanced decisionmaking skills to help them optimally manage pain.…”
Section: Implications For Nursing and Conclusionmentioning
confidence: 99%
“…In particular, Oldenmenger’s systematic review [10] recently performed on 26 Randomised Controlled Trials (RCT) totalling 4735 patients, shows that PEP may result in improvements of relevant patient-reported outcomes. Adam et al [11] analysed 34 RCT and 8 systematic reviews (including 3 meta-analyses [1214]) in the field of cancer pain covering nearly 40 years. Reviews showed a slight but statistically significant effect of PEP on knowledge about pain and attitudes towards it, as well as a decrease in pain intensity as reported by patients.…”
Section: Introductionmentioning
confidence: 99%